2023
DOI: 10.3389/fsurg.2022.1022903
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of CT imaging changes of psoas major muscles in patients with lumbar disc herniation mainly based on low back pain and lower limb pain

Abstract: BackgroundThe study aimed to compare the area changes of CT (computed tomograghy) imaging of psoas major muscle (PM) in patients with lumbar disc herniation (LDH) mainly based on low back pain (LBP) and lower limb pain (LLP), and to analyze the correlation among them.MethodsWe retrospectively analyzed the lumbar CT imaging data of 120 patients with LDH and 60 healthy control people in our hospital from July 2017 to August 2019. They were divided into LBP group (60 cases), LLP group (60 cases) and healthy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…Juraj et al [ 10 ] found in their study on PM in intervertebral disc degeneration that patients with intervertebral disc degeneration and Modic changes had a smaller PM than normal people, and it was inferred that the reduction of activity caused by pain led to a decrease in PM CSA. In this regard, the research of Parkkola et al [ 22 ] and Cui et al [ 23 ] also reached the same conclusion. However, previous studies have not linked the degree of lumbar disc herniation with CSA of PM.…”
Section: Discussionsupporting
confidence: 66%
“…Juraj et al [ 10 ] found in their study on PM in intervertebral disc degeneration that patients with intervertebral disc degeneration and Modic changes had a smaller PM than normal people, and it was inferred that the reduction of activity caused by pain led to a decrease in PM CSA. In this regard, the research of Parkkola et al [ 22 ] and Cui et al [ 23 ] also reached the same conclusion. However, previous studies have not linked the degree of lumbar disc herniation with CSA of PM.…”
Section: Discussionsupporting
confidence: 66%
“…Juraj et al [10 ]found in their study on PM in intervertebral disc degeneration that patients with intervertebral disc degeneration and modic changes had a smaller PM than normal people, and it was inferred that the reduction of activity caused by pain led to a decrease in PM CSA. In this regard, the research of Parkkola [22], Cui [23] et al also reached the same conclusion. However, previous studies have not linked the degree of lumbar disc herniation with CSA of PM.…”
Section: Discussionsupporting
confidence: 58%
“…In cases of radiculopathy, nerves going to the muscles may be affected. In many instances, patients with lumbar disc herniation will have low back pain as their presenting symptom with some pain or loss of sensation in the lower limbs [18].…”
Section: Annular Fissuresmentioning
confidence: 99%
“…In cases of radiculopathy, nerves going to the muscles may be affected. In many instances, patients with lumbar disc herniation will have low back pain as their presenting symptom with some pain or loss of sensation in the lower limbs [ 18 ]. A retrospective analysis of lumbar CT scans of patients with herniated lumbar discs (n=120) and controls (n=60) was analyzed, grouping the disc herniation patients into those who reported lower limb pain (n=60) and those with low back pain (n=60).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation